Needle-free vaccination: formulation and dermal delivery of diphtheria toxin CRM197 mutant - Weissmueller, NT (2013)
The unsafe use of needles propagates cross infections with bloodborne pathogens and reduces the positive impact of vaccinations on global health. While a plethora of needle-free injection devices exist, the reformulation of protein-based vaccines is largely empirical and costly, which presents a barrier to their widespread clinical application. This thesis contributes to the identification of approaches that facilitate rapid vaccine reformulation and enhance the immunogenicity of needle-free dry-powder vaccines with the help of novel antigen delivery platforms. We hypothesised that the thermodynamic stabilisation of diphtheria toxin mutant 197 (CRM197), a glycoconjugate vaccine carrier protein, may enhance its structural preservation during spray-freeze-drying (SFD), and that its formulation in either soluble, surface-adsorbed, or nanoparticle form impacts the elicited immune response. Differential scanning fluorimetry was used to study the effect of excipients on the thermal stability of CRM197. Dry-powder formulation of CRM197 used i) encapsulation into a thermodynamically stabilising excipient matrix by SFD, ii) surface-immobilisation via physisorption onto a novel potassium-doped hydroxyapatite (kHA) carrier microparticle formed by molten salt synthesis, and iii) chemical conjugation and surface presentation on amphiphilic block copolymer nanoparticles that were incorporated into SFD-powders (SFD-NP). The structural integrity of CRM197 was assessed by size separation in addition to various spectral and thermal analysis methods. The immunogenicity of dry-powder CRM197 formulations was subsequently tested in vivo. The results suggest that the thermodynamic stability of CRM197 in solution does not ensure its structural stability during SFD. While needle-free dermal vaccination with kHA-adsorbed CRM197 induced comparable antibody titres to conventional IM injection of alum-adjuvanted CRM197, needle-free SFD and SFD-NP powders were less immunogenic. The highest mean IgG titre and most balanced Th1/Th2 response was achieved with nanoparticle-conjugated CRM197 by IM, which outperformed the current clinical standard. Therefore, future vaccine design should combine thermodynamic and kinetic stability screening, and place special emphasis on the delivery and structural presentation of the antigen to the immune system.